Avaliação comparativa das perdas de água por evapotranspiração em mesocosmos colonizados por diferentes macrófitas aquáticas - Rosa, C. S.; Antunes, R. D.; Pitelli, R. A. [UNESP]; Pitelli, R. l. C. M. (Sociedade Brasileira da Ciência das Plantas Daninhas, 2009)
Water loss increase through evapotranspiration is one the most important modes of interference of weeds in water bodies, especially in water storage reservoirs. Thus, this research was conducted to compare the water losses in mesocosms colonized with the aquatic weeds Myriophyllum aquaticum,Brachiaria subquadripara,Echinochloa polystachya,Typha latifolia and Pontederia lanceolata. The evaluations were carried out in July 2004, in three 4-day periods. The water losses were evaluated based on the amounts of water necessary to restore the existing water level before each evaluation period. The colonization of the aquatic weeds increased the water losses in the mesocosms, with the highest losses being observed in those colonized by T. latifolia, between 3.54 to 4.71 times the water surface without aquatic weeds. The losses in the mesocosms colonized by M. aquaticum,B. subquadripara, E. polystachya, and P. lanceolata were statistically similar and promoted increases between 1.54 to 2.21 times the free surface. The results showed that aquatic weed control is important to prevent water losses in reservoirs used for water storage.

Uma das mais importantes formas de interferência das macrófitas aquáticas em corpos hídricos é o aumento das perdas d'água para a atmosfera pela evapotranspiração. Em alguns corpos hídricos esse aumento pode ser considerado uma interferência negativa e indesejável, especialmente em reservatórios para armazenamento de água e reservatórios de acúmulo para geração de energia elétrica. Assim, este trabalho foi realizado com o objetivo de comparar as perdas d'água em mesocosmos colonizados com macrófitas aquáticas importantes em corpos hídricos no Brasil, mais especificamente Myriophyllum aquaticum, Brachiaria subquadripara, Echinochloa polystachya, Typha latifolia e Pontederia lanceolata. As avaliações foram conduzidas no mês de julho de 2004, em três períodos de quatro dias. As perdas d'água foram avaliadas pelas quantidades necessárias para reposição do nível existente antes do respectivo período de avaliação. A colonização de macrófitas aquáticas aumentou as perdas d'água nos mesocosmos, com maiores valores observados naqueles colonizados por T. latifolia: entre 3,54 e 4,71 vezes a superfície de água sem macrófitas. As perdas nos mesocosmos colonizados por M. aquaticum, B. subquadripara, E. polystachya e P. lanceolata foram estatisticamente similares e promoveram aumentos entre 1,54 e 2,21 vezes a superfície livre. Os resultados evidenciam a importância do manejo de macrófitas aquáticas em corpos hídricos para armazenamento de água.
Comparative evaluation of water losses by evapotranspiration in mesocosms colonized by different aquatic weeds
Keywords: Myriophyllum aquaticum; Brachiaria subquadripara; Echinochloa polystachya; Typha latifolia; Pontederia lanceolata; Myriophyllum aquaticum; Brachiaria subquadripara; Echinochloa polystachya; Typha latifolia; Pontederia lanceolata